When neurologist and patient disagree on reasonable risk: new challenges in prescribing for patients with multiple sclerosis - Kachuck NJ (Dove Medical Press, 2011)
Norman J KachuckUniversity of Southern California, Keck School of Medicine, Los Angeles, CA, USAAbstract: New more powerful therapies for the treatment of multiple sclerosis may also confer a potential for unprecedented life-endangering side effects. How does a physician respond to a patient's request for a treatment the benefit of which cannot be clearly established as worth its risk? The current challenge with prescription of natalizumab (Tysabri®, Biogen Idec) is used to illustrate how this conflict creates an opportunity to re-examine our goals as physicians and the nature of the physician-patient relationship. Understanding the physician's role in that partnership, and the ethical and psychological issues impacting on how reasonable risk is determined, can improve the neurologist's capacity to explicate such quandaries. Redefining what is required to mediate disagreement between doctors and patients about reasonable risk is at the heart of why many of us became physicians. However, such nuanced interpersonal dynamics of patient care can be neglected due to the time and resource pressures of our practices. These demands have increased the seductiveness of the efficiencies promoted by the trend toward the pseudoobjectification of evidence-based care, which has arguably monopolized the healing conversation often to the detriment of the shared narrative. We examine and attempt to reframe the fiduciary and biopsychosocial contretemps of the doctor and patient disagreeing on risk, emphasizing its humanistic, relational dimensions.Keywords: multiple sclerosis, natalizumab, medical ethics, medical decision-making, patient-physician relationship